Gender and Age Differentials in Prevalence and Pattern of Nine Chronic Diseases Among Older Adults in India: An Analysis Based on Longitudinal Ageing Study in India - Mrigesh Bhatia; Laxmi Kant Dwivedi; Priti Maurya; Sameer Dawoodi; Waquar Ahmed; Somnath Jana; Priyanka Dixit (The Journal of Clinical Hypertension)
ABSTRACT Non‐communicable diseases (NCDs) account for a major portion of morbidity and mortality worldwide, with older persons being especially vulnerable due to age‐related health concerns. The burden of chronic diseases among India's aging population is understudied, particularly in terms of gender and age differences. The study utilized data from the Longitudinal Ageing Study in India (LASI), wave 1 (2017–18), comprising a sample of 66,606 older adults aged 45 years and above. We performed a Mmultivariable logistic regression analysis to examine the age‐gender differences in the prevalence and patterns of nine chronic diseases, namely hypertension, diabetes, cancer, chronic heart disease, stroke, psychiatric disorders, chronic lung disease, bone and joint diseases, and high cholesterol among older adults after adjusting for various socio‐demographic and lifestyle factors. Compared to male respondents, female older respondents were less likely to have diabetes and stroke (in the 45–59 and 60–69 years age groups), chronic lung diseases (in the 45–59 years age group), and chronic heart diseases (in the 60–69 years age group). Conversely, in the 70 years and above age group, older female respondents had higher odds of having hypertension and bone and joint diseases compared to male respondents. The current study revealed significant gender and age‐related differences in the prevalence and odds of all the nine selected diseases even adjusted for potential confounding factors. The findings highlight how urgently age‐ and gender‐specific treatments are needed to reduce inequities in chronic diseases, boost positive health outcomes, and improve the quality of life for India's aging populations.